2016
DOI: 10.1007/s00262-016-1869-7
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of synthetic naked RNA by skin-resident dendritic cells via macropinocytosis allows antigen expression and induction of T-cell responses in mice

Abstract: Intradermal administration of antigen-encoding RNA has entered clinical testing for cancer vaccination. However, insight into the underlying mechanism of RNA uptake, translation and antigen presentation is still limited. Utilizing pharmacologically optimized naked RNA, the dose-response kinetics revealed a rise in reporter signal with increasing RNA amounts and a prolonged RNA translation of reporter protein up to 30 days after intradermal injection. Dendritic cells (DCs) in the dermis were shown to engulf RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 19 publications
1
46
0
Order By: Relevance
“…Although DCs have been shown to internalize naked mRNA through a variety of endocytic pathways 6163 , ex vivo transfection efficiency is commonly increased using electroporation; in this case, mRNA molecules pass through membrane pores formed by a high-voltage pulse and directly enter the cytoplasm (reviewed in REF. 64).…”
Section: Recent Advances In Mrna Vaccine Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…Although DCs have been shown to internalize naked mRNA through a variety of endocytic pathways 6163 , ex vivo transfection efficiency is commonly increased using electroporation; in this case, mRNA molecules pass through membrane pores formed by a high-voltage pulse and directly enter the cytoplasm (reviewed in REF. 64).…”
Section: Recent Advances In Mrna Vaccine Technologymentioning
confidence: 99%
“…Naked mRNA has been used successfully for in vivo immunizations, particularly in formats that preferentially target antigen-presenting cells , as in intradermal 61,65 and intranodal injections 6668 . Notably, a recent report showed that repeated intranodal immunizations with naked, unmodified mRNA encoding tumour-associated neoantigens generated robust T cell responses and increased progression-free survival 68 (discussed further in BOX 2).…”
Section: Recent Advances In Mrna Vaccine Technologymentioning
confidence: 99%
“…Hence, it circumvents the need to employ carriers, eventually contributing to reduced cost and potential risk. Another advantage of administering mRNA-based vaccines via the s.c. route is that both cellular and humoral immune responses are induced [94] because the mRNA is expressed by both skin-resident DCs [95] and non-immune cells [96]. However, the outermost stratum corneum layer of the epidermis serves as a tight barrier to the absorption of topically administered drugs [97].…”
Section: Naked Rnamentioning
confidence: 99%
“…To investigate the cellular uptake mechanism of OVA‐Cu‐HVs, different chemical blockers, including cytochalasin D, chlorpromazine, filipin III, and rottlerin, were used to examine the endocytosis pathways for the cell uptake of OVA‐Cu‐HVs . As show in Figure B,C, the uptake of OVA‐Cu‐HVs was significantly suppressed after treatment with rottlerin, indicating that macropinocytosis‐mediated pathway was a major process involved in their cellular uptake …”
Section: Resultsmentioning
confidence: 99%